2017
DOI: 10.1080/1828051x.2016.1275953
|View full text |Cite
|
Sign up to set email alerts
|

Growth and metabolic responses in Nile tilapia (Oreochromis niloticus) subjected to varied starch and protein levels of diets

Abstract: In the present study, six diets were formulated to contain 24% or 36% protein, and 0, 20%, or 40% starch. The Nile tilapias (Oreochromis niloticus) were fed with the designed diets for 56 days. An overall increasing tendency of percent weight gain, feed efficiency, protein efficiency rate (PER), hepatosomatic index (HSI), and condition factor (CF), whole-body protein and lipid contents, plasma concentrations of triglyceride (TG), total cholesterol (T-CHO) and glucose, liver glycogen contents, liver activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 38 publications
6
9
0
Order By: Relevance
“…First, high-carbohydrate diets exerted expected effects on the chemical composition of the liver and muscles: (1) reduced protein in the liver, (2) increased fat in the liver and (3) elevated glycogen in the liver and muscles. Indeed, the effects of high-carbohydrate dietary intake were similar to those in previous reports (Azaza et al, 2015;Wang et al, 2017;Boonanuntanasarn et al, 2018a). Combined with the effects of early glucose stimuli, our results suggested that the hyperglucidic stimulus history modulated the effects of highcarbohydrate diet on the liver composition: early glucose stimuli and high-carbohydrate diets synergistically reduced hepatic proteins, increased hepatic lipids and increased glycogen in the liver and muscles.…”
Section: Long-term Effects Of Early Glucose Injection On Growth Perfosupporting
confidence: 89%
See 1 more Smart Citation
“…First, high-carbohydrate diets exerted expected effects on the chemical composition of the liver and muscles: (1) reduced protein in the liver, (2) increased fat in the liver and (3) elevated glycogen in the liver and muscles. Indeed, the effects of high-carbohydrate dietary intake were similar to those in previous reports (Azaza et al, 2015;Wang et al, 2017;Boonanuntanasarn et al, 2018a). Combined with the effects of early glucose stimuli, our results suggested that the hyperglucidic stimulus history modulated the effects of highcarbohydrate diet on the liver composition: early glucose stimuli and high-carbohydrate diets synergistically reduced hepatic proteins, increased hepatic lipids and increased glycogen in the liver and muscles.…”
Section: Long-term Effects Of Early Glucose Injection On Growth Perfosupporting
confidence: 89%
“…First, as shown in previous studies (Boonanuntanasarn et al, 2018a,b), our results showed that the increase of dietary carbohydrates and the concomitant decrease of dietary proteins are associated with (1) an increase in gck/hk1 (glucose phosphorylation) and fasn-g6pd (lipogenesis) and (2) a decrease in g6pca1, pck1, and pck2 (gluconeogenesis) and in asat, alat and gdh (amino acid catabolism). Moreover, the high glycolytic activity for PK (in the liver and muscles) and HK (muscle) confirmed the good adaptation of tilapia to carbohydrates (Wang et al, 2005(Wang et al, , 2017Figueiredo-Silva et al, 2013;Boonanuntanasarn et al, 2018a,b). The most important and original point here is that early glucose stimuli appeared to synergistically influence liver glycolysis and gluconeogenesis and muscle glucose metabolism.…”
Section: Long-term Effects Of Early Glucose Injection On Growth Perfomentioning
confidence: 59%
“…Regarding the effect of the CHO-H diet, we observed a reduction of hepatic protein and plasmatic BUN, an elevation of hepatic fat and plasma triacylglycerol, and an increase in HSI. These findings were consistent with those reported in previous studies ( 18 , 47 , 48 ) . Notably, intake of an HC diet did not significantly increase postprandial glycaemia, suggesting a high ability of Nile tilapia to regulate glucose homeostasis when fed with carbohydrates, as observed previously in omnivorous fish ( 13 , 16 , 17 , 18 ) .…”
Section: Discussionsupporting
confidence: 94%
“…Tilapia in the malt flour BFT had significantly higher protein content (19.17%) than the other treatments. Wang, Chen, Wang, and Ye (2017) reported similar trend of increased whole body protein and reduced moisture content in tilapia fed diets containing different levels of starch. de Lima et al.…”
Section: Discussionmentioning
confidence: 72%